Association Between Different Metabolic Markers and Metabolic Syndrome in an Outpatient Hyperuricemia Population: A Cross-Sectional Study - Li X; Huang B; Liu Y; Wang M; Wang YX; Feng KL; Cui JQ (Diabetes, Metabolic Syndrome and Obesity, 2023)
Xin Li,* Bo Huang,* Yue Liu, Meng Wang, Yi-Xuan Wang, Kai-Lei Feng, Jing-Qiu Cui Department of Endocrinology and Metabolism, Tianjin Medical University General Hospital, Tianjin, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing-Qiu Cui, Department of Endocrinology and Metabolism, Tianjin Medical University General Hospital, An Shan Dao 154, Tianjin, 300052, People’s Republic of China, Tel +86-13920765604, Email cuijingqiu@tmu.edu.cnBackground: Hyperuricemia (HUA) is often associated with metabolic syndrome (MetS). However, the role of different metabolic markers in the screening of MetS in out-patients with hyperuricemia is unclear. The study aims to investigate the relationship between different metabolic indexes and MetS.Methods: A total of 399 hyperuricemia patients from Tianjin Medical University General Hospital from 2022 to 2023 were included in this study. We collected demographic, anthropometric, and biochemical data on each subject. And calculate serum uric acid-to-creatinine ratio (SUA/Cr), serum uric acid to high-density lipoprotein cholesterol (UHR), triglyceride to high-density lipoprotein cholesterol (THR), and triglyceride and glucose (TyG) index. Binary logistic regression modeling was performed to explore the association between different metabolic markers and MetS.Results: Out of the 399 subjects, 28.3% had MetS. UHR, THR, and TyG index were significantly higher in the MetS group than those in the control group (p< 0.05), which were associated with an increased risk of MetS. However, SUA/Cr was not associated with MetS (p> 0.05). TyG index had a stronger relationship with the risk of MetS (OR 5.476, 95% CI 2.210– 13.569, p< 0.001). The cut-off with the biggest Youden index of the TyG index was 9.13 and the area under the curve (AUC) was 0.719.Conclusion: A high TyG index is associated with an increased risk of MetS in HUA patients. These findings might help screen MetS in individuals with HUA and could be more standardized management of patients with high uric acid in outpatient clinics.Keywords: metabolic syndrome, serum uric acid-to-creatinine ratio, serum uric acid to high-density lipoprotein cholesterol, triglyceride to high-density lipoprotein cholesterol, TyG index